An Extension of the Optimal Homotopy Asymptotic Method to Coupled Schrödinger-KdV Equation - Hakeem Ullah; Saeed Islam; Muhammad Idrees; Mehreen Fiza; Zahoor Ul Haq (International Journal of Differential Equations)
We consider the approximate solution of the coupled Schrödinger-KdV equation by using the extended optimal homotopy asymptotic method (OHAM). We obtained the extended OHAM solution of the problem and compared with the exact, variational iteration method (VIM) and homotopy perturbation method (HPM) solutions. The obtained solution shows that extended OHAM is effective, simpler, easier, and explicit and gives a suitable way to control the convergence of the approximate solution.